Instantaneous axis of helical motion of a rigid body (Международный научный журнал «Инженер», 2026)
This study investigates the state of the instantaneous screw axis (ISA) during the motion of a rigid body. Italso introduces a method for altering the representation of rigid body motion. The paper demonstrates howtranslational and rotational motion parameters of a rigid body can be expressed as functions of the invariantsof instantaneous screw motion (ISM). By using these invariants, a more generalized and compact formulationof rigid body motion is achieved. The approach helps to describe complex motion behaviors with greaterclarity and mathematical efficiency. This framework is applicable to a wide range of mechanical and roboticsystems, offering improved insight into motion analysis and control through ISM-based modeling techniques.